Portrait collection I, II, III – Bellville Magistrate’s Court - Schereka, Wilton (WritingThreeSixty, 2018)
I spent five days at the court trying to get to take pictures inside the hallways, but it was a real struggle as soon as people and security saw the camera. On the last day, I then decided that I would just take the pictures outside and see how they came out. I wanted to do portraits of my parents, who both spent lots of time here during the 80s. My dad, under arrest, and my mom, looking for him. In the end, convincing security that I had no motive other than to do these pictures for a university assignment proved futile. So, I decided to place my parents and the building in context of the road.